2021
DOI: 10.30935/cedtech/11367
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Training for Educational Change: The View of International Experts

Abstract: Digital competence has become a new type of literacy that significantly impacts on people's lives, as it is paramount to their social and occupational integration. In educational institutions, teachers play a major role in developing the digital skills of their students. This study aims to determine the key elements of teacher training in the use of innovative technologies and methodologies with a view to providing alternatives to improve the educational process. The objective is to overcome deficiencies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
7
0
1
Order By: Relevance
“…García et al [5] conducted a study to identify the key elements of teacher training in the use of the latest ICTs, as well as various methodologies, with the aim of providing improvements in the educational process to overcome deficiencies in their professional training. An experimental study conducted by the authors showed that the education of teachers must necessarily be focused on the practical part, and the work of young teachers must be carried out with the help of teachers with experience.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…García et al [5] conducted a study to identify the key elements of teacher training in the use of the latest ICTs, as well as various methodologies, with the aim of providing improvements in the educational process to overcome deficiencies in their professional training. An experimental study conducted by the authors showed that the education of teachers must necessarily be focused on the practical part, and the work of young teachers must be carried out with the help of teachers with experience.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…An experimental study conducted by the authors showed that the education of teachers must necessarily be focused on the practical part, and the work of young teachers must be carried out with the help of teachers with experience. The authors also found that some standards should be approved to monitor the digital competence of teachers [5].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several authors (Bwalya & Rutegwa, 2023;Durdu & Dag, 2017;García et al, 2021;Penn & Mavuru, 2020;Pondee et al, 2021;Sintema & Marbán, 2020;Thohir et al, 2023;Umutlu, 2022) have noted that PSTs have difficulties integrating technology in their classroom practice. For example, Bwalya and Rutegwa (2023) averred that PSTs at two Zambian universities had low to moderate TPACK self-efficacy, possibly due to a lack of training on technology integration in teaching.…”
Section: Introductionmentioning
confidence: 99%
“…A good curriculum must cover aspects of teaching techniques close to actual professional activities, must concentrate on theoretical and simulated strategies, and should meet high standards and expectations of all stakeholders including learners, graduates, and lecturers [102]. Also, knowledge of IoT technologies will prepare internships where students can use IoT [103] or offer access to education and work to underrepresented groups of people and to teachers' training [104].…”
Section: Iot In Energy Education and Other Sectorsmentioning
confidence: 99%